2017
DOI: 10.18488/journal.aefr.2017.78.770.779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macroeconomic Variables on Stock Market Performance of SAARC Countries

Abstract: Article HistoryStock market is one of the most widely followed markets in the world with a horde of transactions facilitated every day. Thus, not surprisingly a plethora of research has been dedicated to understanding the nature of these markets and what factors affect their movements and performance in general. Several studies have postulated that macroeconomic variables do tend to significantly affect stock market performance, while other studies found inconclusive relation at best. It is also worth noting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 11 publications
3
20
4
Order By: Relevance
“…This result is in agreement with the findings of (Talla 2013;Gatsimbazi et al, 2018) while disagreeing with the findings of (Ouma & Muriu, 2014;Giri & Joshi, 2017) whose studies revealed the inflation rate had significant positive impact on share prices. The result also conflicts with the findings of (Barno, 2014;Golam et al, 2017;Khalid & Khan, 2017) whose studies did not find inflation rate influencing share prices.…”
Section: Test Of Hypothesiscontrasting
confidence: 84%
See 4 more Smart Citations
“…This result is in agreement with the findings of (Talla 2013;Gatsimbazi et al, 2018) while disagreeing with the findings of (Ouma & Muriu, 2014;Giri & Joshi, 2017) whose studies revealed the inflation rate had significant positive impact on share prices. The result also conflicts with the findings of (Barno, 2014;Golam et al, 2017;Khalid & Khan, 2017) whose studies did not find inflation rate influencing share prices.…”
Section: Test Of Hypothesiscontrasting
confidence: 84%
“…This result entails that interest rate does not have any significant impact on share price index, therefore, the Ho2 is hereby accepted and the alternative which states otherwise rejected. This result conflicts with the findings of (Nijam et al, 2015;Golam et al, 2017) whose studies provided evidence that interest rate positively influenced share prices. There is also a discrepancy between this result and the findings of (Arnes, 2014;Barno, 2014) whose studies revealed that interest rate had significant negative influence on stock market performance in Turkey and Ghana respectively.…”
Section: Test Of Hypothesiscontrasting
confidence: 82%
See 3 more Smart Citations